Case in Semitic - Hasselbach, Rebecca (Oxford University Press, 2013)
Ebook from Oxford Scholarship Online; Includes bibliographical references and indexes; The Semitic case system: basic evidence and traditional reconstruction -- Linguistic typology -- Grammatical roles and the alignment of Semitic -- Head- and dependent-marking in Semitic -- The function of case markers in Semitic